Corrigendum to "Synthesis, structure-activity relationship and molecular docking studies of 3-O-flavonol glycosides as cholinesterase inhibitors" [Bioorg. Med. Chem. 26 (12) (2018) 3696–3706]. Issue 13 (30th July 2018) - Ullah Mughal, Ehsan; Javid, Asif; Sadiq, Amina; Murtaza, Shahzad; Naveed Zafar, Muhammad; Ahmad Khan, Bilal; Hussain Sumrra, Sajjad; Nawaz Tahir, Muhammad; Kanwal,; Mohammed Khan, Khalid
Graphical abstract: